2021
DOI: 10.6017/ijahe.v8i1.13361
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internationalising the Student Community on Graduate Students' Global Citizenship:

Abstract: This article examines the effect of internationalising the student community on graduate students’ demonstrated commitment to global citizenship at a university in Uganda. It arose from a sequential explanatory survey study. Quantitative and qualitative data were gathered from a sample of 180 graduate students, with the former analysed employing descriptive and inferential statistics, while the latter were analysed using thematic content analysis. The quantitative results revealed that an internationalised stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All in all, several scholars (Ayebare, 2021;Gomes et al, 2014;Nada & Araújo, 2019;Ratshilaya, 2017;Ssempebwa et al, 2014;Zhou & Zhang, 2014) have emphasised the important role of university support services for international student success in higher education. However, none of the above studies explored support services provided to international graduate students in Uganda, particularly Makerere University.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…All in all, several scholars (Ayebare, 2021;Gomes et al, 2014;Nada & Araújo, 2019;Ratshilaya, 2017;Ssempebwa et al, 2014;Zhou & Zhang, 2014) have emphasised the important role of university support services for international student success in higher education. However, none of the above studies explored support services provided to international graduate students in Uganda, particularly Makerere University.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In Uganda, the history of internationalization of higher education can also be traced way back from 1922 when Makerere University was founded as a technical college by the British Colonial Administration (Makerere University, 2019). While some of the Makerere University academic and administrative staff was hired from Europe, there was also a regional structural enrollment of students mainly from Ghana, Kenya, Malawi, Nigeria, Tanzania, Uganda and Zambia (Ayebare, 2021). Internationalization of education at Makerere university was later identified as an important element in the strategic plan of 2008/2009(Makerere University, 2008 This was further supported by the international office which was established in 2005 to spearhead and coordinate internationalization activities at Makerere University (Makerere University, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although labels such as dialogue, multiculturalism, and pluralism have been used to refer to the concept of "cross-cultural communication" (Lin, 2020), it is simply the exchange of information between people of different cultural backgrounds (Morais and Ogden, 2011). The concept is linked to universities' internationalisation agendas (Ayebare and Onen, 2021). Its importance in building a learning community was highlighted by Montagu and Watson (1979) who observed that communication is the "ground of meeting and the foundation of community" (p.vii), without which CRCM and learning for culturally diverse students become challenging to accomplish.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, 48% of student enrolment at Kampala International University (KIU) in the 2013/2014 academic year was international students (National Council for Higher Education [NCHE], 2014), while during the 2019/2020 academic year, international students accounted for 2,599 of the total student population of 10,245 at the Islamic University in Uganda (IUIU) (IUIU, 2019b). These students mainly hailed from Rwanda, Kenya, Nigeria, Somalia, Nigeria, the Democratic Republic of Congo, Eritrea, Sudan, Japan, and Norway (Ayebare and Onen, 2021;IUIU, 2019a). Although the Uganda National Council for Higher Education [NCHE] (NCHE, 2014) revealed a declining trend in international student exchange, the Observatory on Borderless Higher Education (OBHE) 2012 report estimated that around 10% of Uganda's student population were international students (Murphy, 2019).…”
Section: Introductionmentioning
confidence: 99%